2017
DOI: 10.14814/phy2.13113
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and liver glycogen utilization during prolonged lift and carry exercise: male and female responses

Abstract: This study examined the use of carbohydrates by men and women during lift/carry exercise. Effects of menstrual cycle variation were examined in women. Twenty‐five subjects (15 M, 10 F) were studied; age 25 ± 2y M, 26 ± 3y F, weight 85 ± 3 kg* M, 63 ± 3 kg F, and height 181 ± 2 cm* M, 161 ± 2 cm F (* P < 0.0001). During exercise subjects squatted to floor level and lifted a 30 kg box, carried it 3 m, and placed it on a shelf 132 cm high 3X/min over a 3‐hour period (540 lifts) or until they could not continue. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Indeed, initial studies that applied the power of transcriptomics and genetics further stressed male-female differential use of lipids and carbohydrates and pinpointed some of the molecular pathways involved. The transcriptomic profiling and biochemical analyses in rodents indicated that about 10% of the transcriptionally active genes in the liver have a sex-dependent expression; transcripts for the synthesis of triglycerides, cholesterol, and very-low-density lipoprotein (VLDL) particles were more expressed in females while genes for FA oxidation, gluconeogenesis, and glycogen synthesis were predominant in males, further stressing the tendency of females to privilege lipid synthesis and males to create large glycogen stores ( Hagve and Christophersen, 1986 , Ivey and Gaesser, 1987 , Kushlan et al., 1981 , Lorbek et al., 2013 , Mauvais-Jarvis, 2015 , Price and Sanders, 2017 , Tarnopolsky and Ruby, 2001 ). Experiments done with mutants of PPARα (the master regulator of FA oxidation) showed that in PPARα −/− mice the pharmacological inhibition of FA oxidation leads to lipid accumulation and death for hypoglycemia mainly in males, while only 25% of females undergoing the same treatment die because of their major ability to oxidize FAs even in the absence of the PPARα receptor ( Djouadi et al., 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, initial studies that applied the power of transcriptomics and genetics further stressed male-female differential use of lipids and carbohydrates and pinpointed some of the molecular pathways involved. The transcriptomic profiling and biochemical analyses in rodents indicated that about 10% of the transcriptionally active genes in the liver have a sex-dependent expression; transcripts for the synthesis of triglycerides, cholesterol, and very-low-density lipoprotein (VLDL) particles were more expressed in females while genes for FA oxidation, gluconeogenesis, and glycogen synthesis were predominant in males, further stressing the tendency of females to privilege lipid synthesis and males to create large glycogen stores ( Hagve and Christophersen, 1986 , Ivey and Gaesser, 1987 , Kushlan et al., 1981 , Lorbek et al., 2013 , Mauvais-Jarvis, 2015 , Price and Sanders, 2017 , Tarnopolsky and Ruby, 2001 ). Experiments done with mutants of PPARα (the master regulator of FA oxidation) showed that in PPARα −/− mice the pharmacological inhibition of FA oxidation leads to lipid accumulation and death for hypoglycemia mainly in males, while only 25% of females undergoing the same treatment die because of their major ability to oxidize FAs even in the absence of the PPARα receptor ( Djouadi et al., 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Choosing members of the water polo team with similar training schedules allowed for a relatively homogenous response to prolonged exercise and perception of fatigue. [12][13][14] The training routine starts with warm-up laps of 50 m for 5 min, followed by 15 m sprints/underwater dive sequences for 10 min that include 10 s rest intervals between bouts, and reaching an estimated 95% of maximum heart rate capacity. Another 5 min are spent doing water treading, which consists of holding both arms at shoulder level while doing eggbeaters.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…HBCD is widely being used as a pre-, intra-, and/or post-workout supplement by individuals ranging from recreational to professional and elite weight lifters, bodybuilders, and endurance athletes 2 . Notably, it has been well-established that prolonged exercise is limited by the availability of muscle and liver glycogen stores [3][4][5][6][7] . These stores are enhanced with increased carbohydrate intake 3 .…”
Section: Introductionmentioning
confidence: 99%